Malaria Prevalence and Associated Risk Factors in Al Managil city, Aljazeera state, Sudan - Mohamed Ahmed Salah Mohamed Ahmed 1; Hajrhma Ismael Hajrhma Mohammedahmed2; Amgad Albashir Khalid Albashir3; Duha Isam Osman Mustfa1; Mohamed Ali Ahmed Hamid1; Mohamed Hassan Ahmed Kebayer4*; Tafawl Ibrahim Karrar4; Abobaker Mohamed Al Amin Al basher5; Samah AbulGasim Osman Karoum6; Nouh Saad Mohamed7 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Malaria remains a significant public health challenge in Aljazeera State, Sudan, substantially contributing to morbidity, particularly in areas like Al Managil City. This study aimed to determine malaria prevalence and associated risk factors in Al Managil City to inform targeted interventions. Methods: A cross-sectional study was conducted in Al Managil City between August 2022 and April 2023. A random sample of 385 individuals presenting at four healthcare facilities was enrolled. Data on demographics and potential risk factors were collected using a standardized questionnaire. Malaria infection was diagnosed by microscopic examination of thick and thin blood films. Results: The overall malaria prevalence was 63.9% (246/385), with Plasmodium falciparum identified in 98.8% of positive cases. The study population was 54.5% male, and 89.9% resided in rural areas. Age was significantly associated with malaria infection (P = 0.003), with the highest prevalence in those over 15 years (76.2%) and the lowest in children under five years (57.4%). No significant associations were found with gender (P = 0.915) or residency (P = 0.295). Fever was reported in 74.8% of all participants (288/385), with a higher prevalence among malaria-positive cases. Proximity to irrigated agricultue was significantly associated with malaria infection (P = 0.009). Conclusion: This study demonstrates high malaria prevalence in Al Managil City, with P. falciparum predominant in 98.8% of cases. The disproportionately high prevalence in individuals over 15 years (76.2%) highlights the need for targeted interventions in this age group, alongside broader vector control strategies. Proximity to irrigated agriculture is a significant risk factor, emphasizing the need for environmental management. These findings support integrated malaria control strategies, including targeted interventions for at-risk groups, to reduce the malaria burden.